2022
DOI: 10.1039/d1nr06129a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of relative beam–profile-compensated quantum yield of upconverting nanoparticles over a wide dynamic range of power densities

Abstract: The presented work uses a discrete strategy of beam profile compensation to evaluate the local internal quantum yield (iQY) of upconverting nanoparticles (UCNPs) at the pixel level of the beam...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(35 citation statements)
references
References 36 publications
(52 reference statements)
3
32
0
Order By: Relevance
“…Unlikely, the UCL of UCNPs typically does not show saturation, regardless of the number of excitation photons and number of energy transfers involved 21,28 . This behaviour seen in UCNPs, named as anomalous power (density) dependence for the first time by Suyver et al, has been extensively observed experimentally as shown in the literature [20][21][22][27][28][29][30][31][32][33] . Yet, analytical studies exploring the phenomenon are nonexistent, especially with regards to the different power density regimes and the thresholds between them.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Unlikely, the UCL of UCNPs typically does not show saturation, regardless of the number of excitation photons and number of energy transfers involved 21,28 . This behaviour seen in UCNPs, named as anomalous power (density) dependence for the first time by Suyver et al, has been extensively observed experimentally as shown in the literature [20][21][22][27][28][29][30][31][32][33] . Yet, analytical studies exploring the phenomenon are nonexistent, especially with regards to the different power density regimes and the thresholds between them.…”
Section: Introductionmentioning
confidence: 93%
“…Despite their poten-tial, the quantum yield (QY) of UCNPs remains low, especially at low excitation power densities required for biological applications 17 . The internal quantum yield (iQY) is often used as a figure of merit to characterise UCNPs, and is defined as the ratio of number of emitted photons to the number of absorbed ones [18][19][20] . At low excitation power densities the non-linear behaviour of UCL is more pronounced and, as a consequence, the iQY is power density dependent [20][21][22][23] , which adds further complexities to the evaluation of their efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome these issues, upconversion community accesses ultraviolet emission through size control, [32][33] lanthanide dopant tuning, [35] energy transfer manipulation, [36] core-shell structure engineering [37] and excitation pulse regulation. [38] Despite advances, it has met with limited success to obtain strong ultraviolet emission, especially in Nd 3 + -sensitized upconversion nanoparticles under 808 nm excitation. Very recently, our group developed an upconverted excitation lock-in strategy to achieve a remarkable enhancement in ultraviolet emission from Nd 3 + -doped upconversion nanoparticles.…”
Section: Introductionmentioning
confidence: 99%